2017
DOI: 10.1007/s00248-017-1044-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Simulated Climate Warming on the Ectomycorrhizal Fungal Community of Boreal and Temperate Host Species Growing Near Their Shared Ecotonal Range Limits

Abstract: Ectomycorrhizal (ECM) fungi can influence the establishment and performance of host species by increasing nutrient and water absorption. Therefore, understanding the response of ECM fungi to expected changes in the global climate is crucial for predicting potential changes in the composition and productivity of forests. While anthropogenic activity has, and will continue to, cause global temperature increases, few studies have investigated how increases in temperature will affect the community composition of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
30
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 94 publications
3
30
2
Order By: Relevance
“…However, the influence of temperature and root density were reported to affect their distribution (Peay et al 2011;Jarvis et al 2013). Accordingly, manipulated warming was reported to decrease medium-smooth and contact exploration types (Mucha et al 2018). To the best of our knowledge, the effect of precipitation has never been related to exploration-type distribution.…”
Section: Cork Oak Ecmf Community Dependence On Environmental Factorsmentioning
confidence: 88%
See 2 more Smart Citations
“…However, the influence of temperature and root density were reported to affect their distribution (Peay et al 2011;Jarvis et al 2013). Accordingly, manipulated warming was reported to decrease medium-smooth and contact exploration types (Mucha et al 2018). To the best of our knowledge, the effect of precipitation has never been related to exploration-type distribution.…”
Section: Cork Oak Ecmf Community Dependence On Environmental Factorsmentioning
confidence: 88%
“…Interestingly, we found a stronger correlation between the rainiest climates and ECMF richness, while ECMF abundance seemed to be more influenced by temperature than precipitation levels. As no alterations in ECMF richness were observed in response to simulated warming in boreal or temperate tree species, Mucha et al (2018) suggested that warming would have a smaller impact on root symbiotic fungi when precipitation was held constant. We suggest that limitations on the precipitation levels occurring in drier regions could lead to a decrease in ECMF richness, making the driest and warmer sites (southern cork oak forests) more susceptible to environmental filtering than the rainiest and colder sites.…”
Section: Cork Oak Ecmf Community Dependence On Environmental Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Climate change can alter the community composition of ECMF by pushing fungi (Kipfer, Egli, Ghazoul, Moser, & Wohlgemuth, ) or their host plants (Fernandez et al, ) outside their ranges of physiological tolerance (Pickles, Egger, Massicotte, & Green, ). However, most studies to date that have examined ECMF or whole fungal community responses to simulated climate change have found fairly small effects (Fernandez et al, ; Mucha et al, ; Parrent, Morris, & Vilgalys, ; Tu et al, ) relative to natural changes in fungal communities observed along large natural gradients of temperature and precipitation (Jarvis, Woodward, Alexander, & Taylor, ; Nottingham et al, ; Peay et al, ; Talbot et al, ; Tedersoo et al, ). Yet, few datasets currently exist with spatial resolution necessary to make accurate predictions of ECMF response to climate change across relevant geographic regions (Mohan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Patterns and processes governing the biogeographical distributions of organisms in their natural environments can be elucidated across geographical gradients at previously unprecedented scales (Andrew et al., , b). The environmental roles shaping fungal diversity are open for investigation, especially within a backdrop of global change (Fisher et al., ; Pärtel et al., ; Soudzilovskaia et al., ; Titeux et al., ; Mucha et al., ).…”
mentioning
confidence: 99%